Combined Vitamin D, Omega-3 Fatty Acids, and a Simple Home Exercise Program May Reduce Cancer Risk Among Active Adults Aged 70 and Older: A Randomized Clinical Trial - Bischoff-Ferrari, Heike A.; Willett, Walter C.; Manson, JoAnn E.; Dawson-Hughes, Bess; Manz, Markus G.; Theiler, Robert; Braendle, Kilian; Vellas, Bruno; Rizzoli, René; Kressig, Reto W.; Staehelin, Hannes B.; Da Silva, José A. P.; et al. (Frontiers in Aging, 2022)
Objective: To test the individual and combined benefit of vitamin D, omega-3 and a simple home strength exercise program on the risk of any invasive cancer. Design: The DO-HEALTH trial is a three-year, multi-centre, 2x2x2 factorial design double-blind randomized-controlled trial to test the individual and combined benefit of three public health interventions. Setting: The trial was conducted between December 2012 and December 2017 in five European countries. Participants: Generally healthy community-dwelling adults ≥ 70 years were recruited. Interventions: Supplemental 2000 IU/day of vitamin D3, and/or 1 g/day of marine omega-3s, and / or a simple home strength exercise (SHEP) programme compared to placebo and control exercise. Main outcome: In this pre-defined exploratory analysis, time-to-development of any verified invasive cancer was the primary outcome, in an adjusted, intent-to-treat analysis. Results: 2157 participants (mean age 74.9 years; 61.7% women; 40.7% with 25-OH vitamin D below 20 ng/mL, 83% at least moderately physically active) were randomized. Over a median follow-up of 2.99 years, 81 invasive cancer cases were diagnosed and verified. For the three individual treatments, adjusted hazard ratios (HR, 95% CI, cases intervention versus control) were 0.76 (0.49-1.18; 36 vs 45) for vitamin D3, 0.70 (0.44-1.09, 32 vs 49) for omega-3s, and 0.74 (0.48-1.15, 35 vs 46) for SHEP. For combinations of two treatments, adjusted HR were 0.53 (0.28-1.00; 15 vs 28 cases) for omega-3s plus vitamin D3, 0.56 (0.30-1.04; 11 vs 21) for vitamin D3 plus SHEP, and 0.52 (0.28-0.97; 12 vs 26 cases) for omega-3s plus SHEP. For all three treatments combined, the adjusted HR was 0.39 (0.18-0.85; 4 vs 12 cases). Conclusion: Supplementation with daily high-dose vitamin D3 plus omega-3s, combined with SHEP showed a cumulative reduction in cancer risk in generally healthy and active, and largely vitamin D replete adults ≥70 years. Trial Registration: ClinicalTrials.gov Identifier: NCT01745263